1. The problem statement, all variables and given/known data Show that every point on the line v = (1,-1,2) + t(2,3,1) satisfies the equation 5x - 3y - z - 6 = 0 2. Relevant equations 3. The attempt at a solution So what I did was solve the equation v by adding the x,z,and z components to get x = 1 + 2t y = -1 + 3t z = 2 + t So I'm thinking that if I can combine these into one equation that I would end up getting the answer. Problem is I can't figure out how to combine the three equations in an equation with all three variables. I keep getting the function in terms of two variables, or the wrong answer all together. One method I used was solving the z equation for t and then plugging it into the x equation and then the y equation. I tried setting they both equal to zero... t = z -2 y = 3z-7 y - 3z + 7 = 0 x = 2z-3 x - 2z + 3 = 0 y - 3z + 7 = x -2z + 3 y - z - x + 4 = 0 Obviously this isn't the correct answer. What am I doin' wrong here?